2016
DOI: 10.1177/1602400224
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Povidone Iodine and Hydrogen Peroxide on Fracture Healing: A Histomorphometric Study on Rats

Abstract: The 1% povidone iodine solution is recommended as the irrigation adjuvant in fracture surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Thus, 10% PVI was selected to evaluate its effect on cancellous bone union at the osteotomy site in the proximal tibia in the present study. However, 1% PVI did not cause delayed bone union in the previous study [20]. In the present study, 10% PVI, which is a higher concentration than is used at the surgical site in the clinical situation, was also used.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Thus, 10% PVI was selected to evaluate its effect on cancellous bone union at the osteotomy site in the proximal tibia in the present study. However, 1% PVI did not cause delayed bone union in the previous study [20]. In the present study, 10% PVI, which is a higher concentration than is used at the surgical site in the clinical situation, was also used.…”
Section: Discussionmentioning
confidence: 65%
“…In an in vivo study, Husodo et al reported that 10% PVI showed a lower percentage of osseous tissue and a higher percentage of fibrous tissue, indicating delayed bone union of the osteotomy site at the femoral shaft of the rat, evaluating mainly cortical bone [20]. Thus, 10% PVI was selected to evaluate its effect on cancellous bone union at the osteotomy site in the proximal tibia in the present study.…”
Section: Discussionmentioning
confidence: 93%
“…The rat femur fracture model was established on a small-animal operating table on a clean bench. We referred to Husodo et al 9 for this model. Briefly, the rats were fasted for 12 h and not permitted to drink water for 3 h before anesthesia.…”
Section: Methodsmentioning
confidence: 99%
“…The rat femur fracture model was established on a small animal operating table in a super clean bench. We refer to Husodo, K. et al [9] for the rat femur fracture model. Brie y, the rats were fasted for 12 h and banned from drinking water for 3 h before anesthesia.…”
Section: Animalsmentioning
confidence: 99%